Voz ativa, destino escolhido : as eleições de 1989 - Maziero, Arthur Fachini (My University, 2019)
This paper analyzes the electoral programs of the Free Election Propaganda Schedule of the first and second round in the 1989 presidential elections through political history. The objective is to compare the electoral programs broadcast on television between September and December with the voting polls of the Datafolha and IBOPE polling institutes. From this analysis, it is identified some aspects that determined the success or not of the campaign of each presidential candidate. For this, it was observed the discourse, party affiliation, political ideology, participation in social movements, the past of personal and political life, the posture and proposals of each. In addition to electoral propaganda, the economic, educational and health situation of the country during President Jose Sarney's rule was also considered to exploit the changes proposed by the presidential campaigners. Through this analysis, we sought to find out the reasons for choosing the electorate for the next president of the Republic (sic).
Este trabalho analisa os programas eleitorais do Horário Gratuito de Propaganda Eleitoral do primeiro e do segundo turno nas eleições presidenciais de 1989 através da História Política. O objetivo é comparar os programas eleitorais transmitidos na televisão entre setembro e dezembro com as pesquisas de intenção de voto dos institutos de pesquisa Datafolha e IBOPE. A partir dessa análise, são identificados alguns aspectos que determinaram o sucesso ou não da campanha de cada candidato à presidência. Para isso, foi observado o discurso, a filiação partidária, a ideologia política, a participação em movimentos sociais, o passado da vida pessoal e política, a postura e as propostas de cada um. Além da propaganda eleitoral, a situação da economia, educação e da saúde do país durante o governo do presidente José Sarney, também foi considerada para explorar as mudanças propostas pelos presidenciáveis em suas campanhas. Através dessa análise, procura-se descobrir as razões da escolha do eleitorado para o próximo presidente da República (sic).
Keywords: Campanhas eleitorais; História política; Candidatos políticos; Eleições